The relationship between organizational culture and competitive intelligence performance in the context of Eritrean trade and manufacturing industries - Kbrom, Berhane Abraham (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2004.